Phase recovery by using optical fiber dispersion and pulse pre-stretching - Cuadrado Laborde, Christian Ariel (2014)
In this work, the applicability of a recently proposed phase recovery technique is extended, by using temporal pulse pre-stretching. As a proof of concept, the light pulses emitted by a two-stage laser system consisting of a sub-picosecond passively mode-locked fiber laser followed by an erbium-doped fiber amplifier were experimentally analyzed. These results were successfully compared with two indirect phase recovery techniques, both based on the Gerchberg–Saxton recursive algorithm and with the intensity autocorrelation when sub-picosecond light pulses were analyzed.